Deinbollia mosaic virus: a novel begomovirus infecting the sapindaceous weed Deinbollia borbonica in Kenya and Tanzania - Kyallo, Martina M.; Sseruwagi, Peter; Skilton, Robert A.; Ochwo-Ssemakula, Mildred; Wasswa, Peter; Ndunguru, Joseph (Springer, 2017)
Four isolates of a bipartite begomovirus from naturally infected Deinbollia borbonica plants exhibiting yellow mosaic symptoms in Kenya and Tanzania were molecularly characterised. The DNA-A was most closely related to that of tomato leaf curl Mayotte virus (AM701764; 82%), while the DNA-B shared the highest nucleotide sequence identity with that of East African cassava mosaic virus (AJ704953) at 65%. Based on the current ICTV species demarcation criterion for the genus Begomovirus (≥91% sequence identity for the complete DNA-A), we report the full-length genome sequence of this novel bipartite begomovirus. The results reveal additional diversity and reservoir hosts of begomoviruses in East Africa.